Analisis Residu Pestisida dalam Buah Cabai Rawit (Capsicum frutescens L.) di Pasar Keputran Surabaya: Analysis of Pesticide Residues in Cayenne Pepper Fruit (Capsicum frutescens L.) at Keputran Market, Surabaya - Pramhesti, Ken Sari Nimas; Haryanta, Dwi; Susilo, Achmadi (Agrocentrum, 2024)
The use of pesticides is often the primary choice to protect chili pepper plants (Capsicum frutescens L.) from damage caused by pests and diseases. However, excessive and uncontrolled use of pesticides can lead to pesticide residues adhering to the chili peppers (Capsicum frutescens L.). This research is descriptive quantitative, involving a laboratory experiment that uses gas chromatography-mass spectrometry (GC-MS) to measure the amount of pesticide residues on chili peppers (Capsicum frutescens L.). The study found that insecticides with active ingredients Chlorpyrifos and Profenofos are the most frequently used by farmers, with applications occurring twice a week. The levels of pesticide residues on chili peppers (Capsicum frutescens L.) show significant variation among samples. Based on the results and discussion, it can be concluded that: the average residue level of Chlorpyrifos on chili peppers sold at Keputran Surabaya market is 3.13 ppm, while Profenofos has an average of 3.25 ppm. Furthermore, the average residue level of Chlorpyrifos in the chili pepper samples from Keputran Market in Surabaya exceeds the Maximum Residue Limit (MRL) established by the Indonesian National Standard (SNI), which is 0.5 ppm. Additionally, the average residue level of Profenofos also exceeds the established MRL, which is 2.0 ppm.